On the essence of systems in general and social systems - Gustavo de Jesús Pérez Durán, (Technium Social Sciences Journal, 2020)
The concept of system has been the basis for deepening the analysis of many natural, mechanical and social phenomena. However, its applications and developments have been based on a very simple definition: complex of interacting components; on which free and imaginative interpretations of the meaning and nature of the components and interaction have been used. The exaggerated and lax use of the concept of system has not only led to many false conclusions, but it has deteriorated its true value and usefulness. In this paper a stricter definition arises and accurate picture of what is a system, in order to limit its application and constrain its use to those phenomena that contain the elements that make up a system and its application is analyzed in the study of systems created by human beings, social systems and natural systems.